Spontaneous Movements of a Computer Mouse Reveal Egoism and In-group Favoritism - Maliszewski, Norbert; Wojciechowski, Łukasz; Suszek, Hubert (Frontiers in Psychology, 2017)
The purpose of the project was to assess whether the first spontaneous movements of a computer mouse, when making an assessment on a scale presented on the screen, may express a respondent’s implicit attitudes. In Study 1, the altruistic behaviors of 66 students were assessed. The students were led to believe that the task they were performing was also being conducted by another person and they were asked to distribute earnings between themselves and the partner. The participants performed the tasks under conditions with and without distractors. With the distractors, in the first few seconds spontaneous mouse movements on the scale expressed selfish distribution of money, while later the movements gravitated towards more altruism. In Study 2, 77 Polish students evaluated a painting by a Polish/Jewish painter on a scale. They evaluated it under conditions of full or distracted cognitive abilities. Spontaneous movements of the mouse on the scale were analyzed. In addition, implicit attitudes towards both Poles and Jews were measured with the Implicit Association Test (IAT). A significant association between implicit attitudes (IAT) and spontaneous evaluation of images using a computer mouse was observed in the group with the distractor. The participants with strong implicit in-group favoritism of Poles revealed stronger preference for the Polish painter’s work in the first few seconds of mouse movement. Taken together, these results suggest that spontaneous mouse movements may reveal egoism (in-group favoritism), i.e. processes that were not observed in the participants’ final decisions (clicking on the scale).